Characterization of macro- and microminerals from farming residues treated with two bioferments - Saavedra Sarmiento, Heráclides Hugo; González Puetate, Iván; Rojas Paredes, Marco Antonio; Pérez Mendoza, Guder Elvira; Robles Huaynate, Rizal Alcides (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2023)
The present work was carried out at the Livestock Waste Utilization Unit of the Faculty of Animal Husbandry of the Universidad Nacional Agraria de la Selva, Peru. The objective was to evaluate the quality of agricultural residues with Mountain Bioferment (T1) and agricultural residues with Bambusal Bioferment (T2), using a complete randomized design (CRD) with two treatments and 6 replicates evaluated at the end of the composting process (37 days). The treatments under study were evaluating the quality of the compost with the parameters of temperature dynamics, pH and chemical characteristics (macro and microminerals) of the compost obtained. The evaluations of macro minerals did not show differences in nitrogen content, although there were differences (p>0,05) in phosphorus (P2O5) for T1 with 0,39%, in potassium (K2O) for T2 with 1,35%, in calcium (Ca) for T1 with 0,71% and in sodium (Na) for T2 with 0,07%. In the microminerals evaluations, T2 stood out for containing higher amounts of Cu, Mn and Zn, compared to T1. It is concluded that both bioferments act in a similar way in the quality of the compost, due to the fact that they contain their own characteristics.